Implementation of Radio Broadcasting Instructional Design as Part of Curriculum for Supporting Students’ Radio Broadcasting Skill in English Department, State Polytechnic of Padang - Sumira Sumira; Difiani Apriyanti (Journal Polingua: Scientific Journal of Linguistics, Literature and Language Education, 2017)
Workshop of English Radio Broadcasting is one of the subjects provided by English Department, State Polytechnics of Padang. The instructional design or syllabus of this subject is designed by English lecturers and continued by coloborating it with professional broadcasters from radio stations. In order to produce skillful  students in English Radio Broadcasting,  it is the duty  for the lecturers to make sure wheather the objective  in the instructional design has been achieved or not. Therefore, this descriptive qualitative and descriptive quantitative research is conducted to find the result. The data of the research which is applied in odd semester of academic period 2015-2016 is collected through observing the class activities and from the students Mid Test and Final Semester Test. The observation is supported by some instruments. After getting all the data, the instructional design is elaborated into checklist note. The data is then being assessed by professional radio broadcaster through intrerview. At last, the data is analyzed qualitatively. The result is most of the students have fulfilled  to be a  radio broadcaster, but they are not in the level of professional. It can be caused of lack practicing and it has to be delivered in English. However, these activities are a good media for students to practice their English especially for writing and speaking skills